Penerapan Metode Tahsin untuk Meningkatkan Kemampuan Membaca Al-Qur’an Siswa Sekolah Menengah Atas - Della Indah Fitriani; Fitroh Hayati (Jurnal Pendidikan Islam Indonesia, 2020)
This research was motivated by the poor of students’ ability in class X IPS SMA Al-Falah Dago in reading and writing Al-Qur'an (BTAQ). It aims, first, to know how the objective conditions of their Al-Qur'an reading ability. Second, to find out how to apply the tahsin method to improve their Al-Qur'an reading ability. Third, to find out how is the effect of the tahsin method implementation to improve their Al-Qur'an reading ability. It was a quantitative study using the experimental method. The results of this study had indicated that the implementation of the tahsin method had a significant effect on improving their Al-Qur'an reading ability which is applicable to the correct makharijul huruf and tajwid rules. The teacher was using classical reading and listening (KBS) in the teaching and learning process. They also were participating to exemplify good reading and to justify the students' reading.